Pengelolaan Keuangan Yang Tranparan Dan Akuntabel Bumdes Di Desa Rajik - Saputra, Darman; Wibawa, Dian Prihardini; Guspian, Iza; Azelya, Iis (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The purpose of this community service activity is to overcome the main problems in the management of Village-Owned Enterprises (BUMDes) in Rajik Village, where most of the managers have limited knowledge and ability in administration and financial reporting. Methodology/approach: The methodology used is participatory training and mentoring, which actively involves all parties. This approach is carried out through material presentations, question and answer sessions, and direct assistance in compiling financial statements of BUMDes in Rajik city. Results/findings: The results of this activity show that well-managed BUMDes can have a positive impact on the village economy. The existence of a well-organized financial system can increase the credibility and sustainability of BUMDes, avoid misuse of funds, and get wider support from the government and the public. Participants showed high enthusiasm and hoped for continuous assistance to improve their financial management. Conclutions: BUMDes have an important role as a driver of the village economy, but their success depends heavily on transparent and accountable financial management. Therefore, continuous technical guidance and training are needed so that BUMDes can continue to develop and provide real benefits to the village community. Limitations: This service is limited to increasing human resource capacity and socializing financial management, without touching the implementation of an integrated accounting system which is still a challenge for BUMDes. Contribution: The main contribution of this service is to increase the understanding of village managers and stakeholders about the best practices of managing BUMDes that are transparent, accountable, and sustainable.